The Mixing of a River into Coastal Waters at Two Beaches: Environmental Factors, E. Coli Contributions and Applications for Predictive Models - (:unkn) unknown (My University, 2015)
Beach closures and public health protection are confounded by analytical procedures that result in delays in notification of adverse water quality conditions and the lack of affordable analytical methods to identify pollutant sources. Attempts have been made to develop predictive frameworks using ancillary hydrometeorological data to statistically anticipate deteriorated water quality. Many urban coastal beaches are impacted by river runoff. In Kenosha Wisconsin, beach sanitary survey data from two beaches adjacent to the mouth of the Pike River were examined to ascertain whether simple river-lake mixing models identified river influence on coastal water quality and improved predictions of beach advisories. Water samples (798 water samples) were collected from the Pike River (one location) and Lake Michigan beach locations to the north (three locations) and south (four locations) of the inflow during the summer months of 2012-2014. Specific conductivity was used as a conservative tracer for quantifying river-lake mixing. Mixing was dependent upon distance from the river mouth, river discharge, and wind and alongshore current directions (p
Keywords: Beach; E. Coli; Mixing; Predictive Model; River; Specific Conductivity